Preservation of the properties of elastic plasma protein plus platelet film for wound dressing. Issue 6 (December 2013) - Sano, Hitomi; Ichioka, Shigeru; Minamimura, Ai; Tanaka, Ryuhei; Ikebuchi, Kenji; Suzuki, Miho
Abstract: Experimental results have previously been reported for a new biological dressing consisting of concentrated plasma proteins and platelet-rich plasma (PRP), which is named Platelet-Protein film (PPF). Based on the results of this experimental study, a clinical trial was begun to examine the usefulness of PPF. Although fresh autologous PPF is being used in the clinical trial, it is considered that the use of a preserved material prepared in advance would enable more convenient application. To verify the usefulness of preserved PPF, this preliminary study was conducted to examine the effects of fresh PPF, preserved PPF or blood clot, as control, applied to excisional skin defects in healing-impaired mice. The wound area and vascular density were analysed on day 9 after wound creation. Significant decrease of the wound size was observed in the preserved PPF and fresh PPF groups (4.2 (3.7), 2.2 (0.53)%) in comparison with that in the control group (38.5 (18.6)%, p < 0.05). Furthermore, a significant increase of the vascular density was also observed in the preserved PPF and fresh PPF groups (0.055 (0.021), 0.050 (0.019) mm 2 /mm 2 ) as compared with that in the control group (0.016 (0.010) mm 2, p < 0.01). There was no significant difference in the effect on the wound size or vascular density between the preserved PPF and fresh PPF groups. The results showed that the properties of PPFs could be maintained for at least 1 week under appropriate storage conditions. The possibility of preservation of PPF for future use could be of practical advantage in actual clinical situations.